Perceptions of self-assessment literacy and self-directed reflection during online learning for Iranian EFL student teachers. Issue 6 (2nd November 2022) - Arefian, Mohammad Hossein
ABSTRACT: During the Covid-19 pandemic, student teachers had to master, reflect, and evaluate individually due to the remote online learning process. Self-assessment literacy and self-directed reflection have turned into tools for autonomous learning during unmonitored online learning processes. An investigation of student teachers' self-assessment literacy and self-directed reflective practices can shed light on their significant applications during unmonitored online learning experiences. This qualitative study investigated 15 Iranian English language student teachers with a semi-structured interview and theme-based analysis to gain in-depth information about their processes and experiences. The results showed that student teachers gained benefits such as preparing before the class, setting aims and objectives, checking, reflecting, modifying on previous learning, acquiring specific knowledge and skills, filling the gap, having self-reflection individually, planning and adapting their actions and performance to reach an ideal self, controlling emotional factors, enhancing own confidence by self-motivational remarks, and creating unrestricted learning opportunities.